2019
DOI: 10.2147/lra.s193925
|View full text |Cite
|
Sign up to set email alerts
|

<p>Spinal anesthesia-induced hypotension is caused by a decrease in stroke volume in elderly patients</p>

Abstract: Background Hypotension is common during spinal anesthesia (SA) and is caused by a decrease in systemic vascular resistance (SVR) and/or cardiac output (CO). The effect of the dose of bupivacaine administered intrathecally on the changes in CO in elderly patients is largely unknown. This study investigated the hemodynamic effect of SA in elderly patients by studying the effect of two different dosages of intrathecal bupivacaine. Methods This prospective cohort study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 32 publications
0
34
0
10
Order By: Relevance
“…In our study, patients receiving the combined spinal-epidural anesthesia also had significantly greater hemodynamic variations compared to those receiving general anesthesia with LMA and nerve block. Spinal anesthesia can inhibit the sympathetic nerves, leading to peripheral vascular dilation and hypotension [8][9][10]. In addition, vagus nerve dominance and slow heart rate during spinal anesthesia may also result in significant hemodynamic variations.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients receiving the combined spinal-epidural anesthesia also had significantly greater hemodynamic variations compared to those receiving general anesthesia with LMA and nerve block. Spinal anesthesia can inhibit the sympathetic nerves, leading to peripheral vascular dilation and hypotension [8][9][10]. In addition, vagus nerve dominance and slow heart rate during spinal anesthesia may also result in significant hemodynamic variations.…”
Section: Discussionmentioning
confidence: 99%
“…In elderly patients undergoing hip fracture repair, continuous spinal anesthesia (CSA) provided fewer episodes of moderate-to-severe hypotension when compared with a single intrathecal injection of 7.5 mg bupivacaine [89]. A prospective cohort study showed that cardiac output and blood pressure decreased significantly after the onset of SA in elderly patients, mainly due to a decrease in stroke volume and not in systemic vascular resistance [90]. A 2014 prospective randomized study of elderly highrisk patients undergoing hip replacement surgery showed that CSA and psoas compartment sciatic nerve block (PCSNB) produced a satisfactory quality of anesthesia.…”
Section: Mode Of Anesthesiamentioning
confidence: 99%
“…3 Keadaan ini disebabkan oleh karena blokade simpatis yang lebih tinggi pada bupivakain hiperbarik (T5) menyebabkan paralisis pada serabut preganglionik saraf simpatis yang kemudian mentransmisikan impuls motorik ke otot polos pembuluh darah perifer. 16,17 Arteri dan arteriol akan mengalami dilatasi pada daerah-daerah yang mengalami denervasi simpatis sehingga resistensi vaskular perifer dan tekanan arteri rata-rata akan mengalami penurunan. Terjadi dilatasi pada vena dan venule perifer dengan pengumpulan darah akan menurunkan curah balik ke jantung sehingga akan menyebabkan penurunan curah jantung dan tekanan darah.…”
Section: Volume 11 Nomor 3 Tahun 2019unclassified